2023
DOI: 10.1021/acsapm.2c02019
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Low-Cost, and Room Temperature Ammonia Sensor Based on Polypyrrole and Functionalized MWCNT Nanocomposites in Extreme Bending Conditions

Abstract: We report a flexible and room temperature ammonia sensor based on polypyrrole/functionalized multiwalled carbon nanotubes (Ppy/f-MWCNTs). This nanocomposite has been synthesized by the in-situ chemical oxidative polymerization method and finally loaded on a transparent poly(vinylidene fluoride) (PVDF) membrane substrate. The entire flexible sensor fabrication process was cost-effective and easy to operate, making it ideal for commercial production on a wide scale. The optimized Ppy/f-MWCNT-based flexible senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Tiwari et al 21 presented a PPy/rGO thin-film-based NH 3 sensor and showed improved sensor durability and response after incorporating rGO. Our group also reported PPy/MWCNT and PPy/f-MWCNT based room temperature ammonia sensors, which exhibit superior gas sensing performance compared to bare polypyrrole 22 , 23 . However, the conventional carbon nano-materials based sensor has several issues, including insensitivity at low target gas concentrations, long response/recovery time, and poor selectivity.…”
Section: Introductionmentioning
confidence: 84%
“…Tiwari et al 21 presented a PPy/rGO thin-film-based NH 3 sensor and showed improved sensor durability and response after incorporating rGO. Our group also reported PPy/MWCNT and PPy/f-MWCNT based room temperature ammonia sensors, which exhibit superior gas sensing performance compared to bare polypyrrole 22 , 23 . However, the conventional carbon nano-materials based sensor has several issues, including insensitivity at low target gas concentrations, long response/recovery time, and poor selectivity.…”
Section: Introductionmentioning
confidence: 84%
“…The information in Table 1 represents the recent trends of various materials towards the sensing of hazardous materials by electrochemical method [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Biosensorsmentioning
confidence: 99%
“…The prepared materials could be the potential candidate for the biosensor application [72]. The information in Table 1 represents the recent trends of various materials towards the sensing of hazardous materials by electrochemical method [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. The information in Table 1 represents the recent trends of various materials towards the sensing of hazardous materials by electrochemical method [73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Cholesterol Sensormentioning
confidence: 99%
“…Major drawbacks associated with these types of gas sensors are their bulkiness, high operating temperature, and complexity in nature. , To overcome these drawbacks, flexible gas sensors have recently gained considerable attention among the research communities for their usage in wearable electronics like smartwatches, bands, human skins, robots, and so on because of their attractive properties, including low-cost, lightweight, compactness, and real-time monitoring of toxic gases without any requirement of special conditions. , Flexible gas sensors are usually made up of electrodes, sensing materials, and a flexible substrate. Paper, polyethylene naphthalate, poly­(ethylene terephthalate) (PET), polyimide, poly­(dimethylsiloxane), polyester film, etc., are the substrates that are most often employed because of their unique properties such as biocompatibility, portability, flexibility, and so forth. , The chemiresistive-based flexible gas sensors have been widely utilized to detect various harmful gases like ammonia (NH 3 ), nitrogen dioxide (NO 2 ), and volatile organic compounds (VOCs) at room temperature (RT). …”
Section: Introductionmentioning
confidence: 99%